Is it sound policy or fast policy? Practitioners' perspectives on the role of place branding in local economic development. Issue 8 (14th September 2017) - Cleave, Evan; Arku, Godwin; Sadler, Richard; Gilliland, Jason
ABSTRACT: In response to neoliberal policies and globalization pressures over the past three decades, urban governments in advanced economies have, with near-unanimity, adopted place branding as an approach to foster local economic growth. Framed as an outcome of multilevel neoliberal policymaking and local entrepreneurial governance, place branding has been adopted by urban places at all scales and geographic contexts with little regard for its efficacy. It is unclear, however, whether place branding represents a substantive approach, or is merely an emerging example of a neoliberal scripting. In many regards, the debate surrounding place branding is similar to the discourse on the Creative Class a decade ago. Consequently, uncertainty exists regarding whether place branding reflects practical and responsible urban governance or a superficial, fast policy with limited potential to foster local development. To date, little is known about how practitioners perceive place branding as a policy tool in the context of economic development. This study examines the perceptions of economic development practitioners regarding how place branding is being developed and implemented as a policy tool. The analysis is based on in-depth interviews with economic development practitioners (n = 25) from a wide range of municipalities in Ontario. Findings of this study indicate that while opportunity exists for place branding to represent in-depth and extensive local development policy, it is more generally an urban development script for creating a sense of place and fostering local economic development. Additionally, the majority of place branding policy represents superficial policy, emphasizing hegemonic approaches. Place branding can therefore be explained as an example of fast policy.